Intrusion detection and correlation : - Kruegel, Christopher (Springer, 2005)
Intrusion Detection and Correlation: Challenges and Solutions presents intrusion detection systems (IDSs) and addresses the problem of managing and correlating the alerts produced. This volume discusses the role of intrusion detection in the realm of network security with comparisons to traditional methods such as firewalls and cryptography." "Intrusion Detection and Correlation: Challenges and Solutions is designed for a professional audience composed of researchers and practitioners in industry. This book is also suitable for graduate-level students in computer science